A MoS2 nanosheet-coated mesh for pH-induced multi-pollutant water remediation with in situ electrocatalysis. Issue 15 (23rd March 2018) - Qu, Ruixiang; Liu, Na; Chen, Yuning; Zhang, Weifeng; Zhang, Qingdong; Liu, Yanan; Feng, Lin
Abstract : A brand new MoS2 nanosheet-coated copper mesh with multi-pollutant degradation properties as well as oil/water separation capabilities was fabricated. Abstract : Herein, a MoS2 nanosheet-coated copper mesh was fabricated by a simple hydrothermal reaction, which could be used for multi-pollutant degradation via electrocatalysis as well as for oil removal from wastewater. Multiscale morphologies were formed by corroding a copper substrate with active sulfur, providing the mesh with super wettability and high specific surface area. Low-voltage electrocatalytic tests revealed that the pH value had various influences on the degradation of dyes and pesticides due to competition between the migration rate and the ionization rate of pollutant molecules. Combining the super wetting behavior and electrocatalytic properties, the MoS2 -coated copper mesh could realize in situ oil removal and multi-pollutant degradation under 12 V in several minutes. The mesh was also reusable (more than 20 times) and chemically stable; this enhanced its potential for applications in industrial and domestic water treatment.